2012
DOI: 10.9738/cc88.1
|View full text |Cite
|
Sign up to set email alerts
|

Successful Combination Therapy of Radical Liver Resection With 5-Fluorouracil/leucovorin, Oxaliplatin, Plus Bevacizumab for Ascending Colon Cancer With Pulmonary and 43 Liver Metastases: Report of a Case

Abstract: At the time of diagnosis, 20% to 25% of patients with colorectal cancer already have liver metastases, the presence of which is a most important prognostic factor. A 64-year-old man was admitted to our hospital for investigation of anemia and multiple liver tumors. Examinations revealed ascending colon carcinoma with more than 40 liver metastases and 2 lung metastases. We performed right hemicolectomy with lymph node dissection, which was followed by 5-fluorouracil/leucovorin, oxaliplatin, plus bevacizumab (FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Around 20-25% of patients initially diagnosed with colorectal carcinoma present with liver metastases ( 100 ). Of these, 80–90% have multiple organ metastasis, including liver, and 50% have exclusively liver metastasis ( 101 ).…”
Section: Liver Metastasesmentioning
confidence: 99%
“…Around 20-25% of patients initially diagnosed with colorectal carcinoma present with liver metastases ( 100 ). Of these, 80–90% have multiple organ metastasis, including liver, and 50% have exclusively liver metastasis ( 101 ).…”
Section: Liver Metastasesmentioning
confidence: 99%
“…The liver is the most common site of CRC metastasis and upwards of 25% of patients with colorectal cancer will have liver metastases at the time of initial diagnosis 52. For those with resectable disease, liver metastasectomy can be performed before, after, or simultaneously with the primary tumor resection, although the addition of neoadjuvant chemotherapy with surgery in otherwise acceptable liver resection candidates has been shown to mildly increase progression-free survival by 9% and can be given some consideration 53.…”
Section: Response To Treatment: Metastasesmentioning
confidence: 99%
“…The liver is the most common site of CRC metastasis and upwards of 25% of patients with colorectal cancer will have liver metastases at the time of initial diagnosis. 52 For those with resectable disease, liver metastasectomy can be performed before, after, or simultaneously with the primary tumor resection, although the addition of neoadjuvant chemotherapy with surgery in otherwise acceptable liver resection candidates has been shown to mildly increase progression-free survival by 9% and can be given some consideration. 53 It is important to remember that overall survival after liver resection is not related to the response to chemotherapy, but is largely a function of the original staging at time of initial diagnosis with a significantly higher five-year survival for those with Stage 1 or 2 disease versus those with Stage 3 or 4 disease (83.9% vs. 35.7%).…”
Section: Response To Treatment: Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer (CRC) is one of the most common malignant tumors in the world, and liver metastasis is the most common form of CRC metastasis ( 1 ). Studies have shown that liver metastasis can occur in ~20% of newly diagnosed CRC patients within half a year ( 2 , 3 ). In addition, >50% of patients with advanced CRC have a median survival of only 21.3 months ( 4 ).…”
Section: Introductionmentioning
confidence: 99%